The Influence of Fashion Technology Courses on the Learning Outcomes of Children's Fashion Production Courses on Students of the Class of 2023 of the Fashion Education Study Program, Semarang State University - Melinda Novitasari; Adhi Kusumastuti (Jurnal Penelitian Pendidikan, 2026)
Vocational education in fashion aims to equip students with theoretical knowledge and practical skills relevant to the demands of the industry. In the Fashion Education curriculum, Fashion Technology is positioned as a basic course that supports applied courses such as Children's Fashion Production. This study aims to examine the influence of the learning outcomes of the Fashion Technology course on the learning outcomes of students in the Children's Fashion Production course. This study uses a quantitative approach with an ex post facto design. The population consists of 82 students of the class of 2023 of the Fashion Education Study Program at Semarang State University, and a total sampling method was used. Data is collected through documentation of student academic data records. Data analysis included descriptive statistics and inferential analysis using simple linear regression with SPSS version 26. The results of the regression analysis showed that the learning outcomes of Fashion Technology had a significant positive influence on the learning outcomes of Children's Fashion Production (F = 24.655; p < 0.05). The coefficient of determination (R²) was 0.233, indicating that Fashion Technology contributed 23.3% to the variance in student achievement in Children's Fashion Production. The regression coefficient (B = 0.457) showed that higher achievement in Fashion Technology was associated with better performance in applied courses. These findings affirm the importance of Fashion Technology as a foundational course that supports students' success in practical fashion production and highlight the need for strong alignment between basic and applied courses in fashion vocational education.